High glucose, but not testosterone, increases platelet aggregation mediated by endothelial cells - Ikhlas Muhammad Jenie (2015)
Endothelial cells inhibit platelet aggregation by releasing thromboregulators, such as prostacyclin and nitric oxide. Male subject is a traditional risk factor for cardiovascular diseases. Platelet hyperreactivity has been frequently found in patient with diabetes mellitus. To examine whether testosterone and high glucose modify platelet aggregation through endothelial cells, we did an in vitro study using endothelial cells culture from human umbilical vein (HUVEC). Treatments were performed in HUVEC sub culture as either normoglucose (5.6 mM) or high glucose (22.4 mM) medium, with or without testosterone (0, 1, 10, 100 nM), for 24 hours. HUVEC were trypsinized, resuspended, and then incubated with platelet rich plasma from healthy male donors with ratio 1:104 for 3 minutes. Platelet aggregation measured by turbidimetry methode. This study showed that testosterone did not significantly influence platelet aggregation through endothelial cells in normoglucose (p = 0.144) or high glucose (p = 0.916) medium. There was no main effect of testosterone (p = 0.73) as well as no interaction between testosterone and glucose (p = 0.69), but there was a main effect of glucose (p = 0.004), to platelet aggregation through endothelial cells. In conclusion, high glucose, but not testosterone, increases platelet aggregation mediated by endothelial cells.